Prevalence of Risk Factors for the Metabolic Syndrome in the Middle Income Caribbean Nation of St. Lucia. (21st September 2014) - Cherry, Colleen O'Brien; Serieux, Elizabeth; Didier, Martin; Nuttal, Mary Elizabeth; Schuster, Richard J.
Abstract : The objective of this research was to measure the presence of metabolic syndrome risk factors in a sample population in the middle income Caribbean nation of St. Lucia and to identify the demographic and behavioral factors of metabolic syndrome among the study participants. Interviews and anthropometric measures were conducted with 499 St. Lucians of ages 18–99. Descriptive statistics were used for the analysis. Fifty-six percent of females and 18 percent of males had a waist size equal to or above the indicator for the metabolic syndrome. Behavioral risk factors such as sedentary lifestyle, smoking, and alcohol consumption varied by gender. Thirty-six percent of women and 22% of men reported a sedentary lifestyle and 43% of women and 65% of men reported any alcohol consumption. More research should be done to determine the cultural norms and gender differences associated with modifiable risk behaviors in St. Lucia.